Kesan penggunaan teknologi maklumat ke atas kualiti kerja - Azlina, binti Mejeni. (Universiti Malaysia Sarawak (UNIMAS), 2002)
Generally, the research aims to perform a preliminary investigation into the usage ofinformation technology in an organization and its impact towards the quality of work. This research was conducted at Jabatan Kesihatan Negeri Sarawak in Kuching. Questionnaires were used as a methodology to collect data from the respondents. The respondents were selected randomly within the organization. 70 sets ofquestionnaires were distributed and unfortunately there were only 45 respondents returned it. Data were analyzed using the Stalistical Package For Social Science (SPSS) /0.0. Descriptive statistics were used to determine the demographic factors of the respondents. One-way ANOVA were used to determine whether there are sighificant differences between age, job position and experience in computer usage with quality ofwork. Data shows that there are no significant differences between age (p=0.200) and experience in computer usage (p=0.349) with quality of work. Pearson Correlation test were used to determine the significant relationship between attitude and work environment with the quality ofwork. Data showed that there was a strong relation between work environment and the quality of work (r=0.854). These findings showed that the work environment would affect the usage of information technology on quality of work. A weak relation between attitude and quality ofwork (r=0.167) cannot be ignored. Positive reaction for competency and skill showed that the respondents agreed that computer usage could help to improve their work quality. Variables ill attitude could be expand to get the relation between attitude and quality ofwork.